Improving the surge capacity of an infectious disease and tropical medicine specialty hospital through the application of flexibility and acuity-adaptability concepts - Roberto, Ronnie Vience P.; David Xander T. Lacson (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
The COVID-19 pandemic revealed the weaknesses of the Philippine healthcare system as the abrupt increase in cases placed unprecedented stress on hospitals and highlighted the need for facilities to adapt rapidly. Despite measures taken to respond to new space requirements, the design of Philippine hospitals demonstrated a lack in surge capacity. The pandemic has provoked a change in ways of thinking about hospital design, and the various interpretations of hospital flexibility are currently being explored for the post-pandemic context. The project aims to explore how an infectious disease specialty hospital can be designed to build surge capacity and facilitate rapid adaptive response. Principles of infection control, acuity adaptability, and flexibility were explored to target challenges revealed in the pandemic concerning patient intake and isolation. Scoping literature reviews were used to synthesize a catalog of design strategies for infection control, acuity adaptability, and flexibility. Additionally, key informant interviews were conducted to provide contextually rich information on the challenges faced by hospitals during the COVID-19 pandemic. Data-gathering revealed three main issues: (1) difficulties in locating COVID patients to prevent transmission to non-COVID patients and healthcare workers, (2) a low degree of transformability in hospitals hindered by the building conformation, and (3) an overall lack of space for patient intake. To address these, infection control and acuity adaptability concepts were specifically applied to address isolation issues, and kinetic architecture concepts were applied to address flexibility and patient intake issues. The project further proposes zoning the hospital according to risk level, acuity, and care requirements to create a responsive facility capable of compartmentation and isolation whenever necessary. The design aims to help guide the design of hospitals in building surge capacity for disruptive epidemiological events. The architectural prototype encourages a rethinking of healthcare facilities in the Philippines, diversifying the approach on hospital architecture with its new applications of known interventions.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Health facilities; Communicable diseases